2020
DOI: 10.3390/nano10061246
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Pneumocystis Pneumonia Diagnosis in Human Samples Using a Label-Free Plasmonic Biosensor

Abstract: Pneumocystis jirovecii is a fungus responsible for human Pneumocystis pneumonia, one of the most severe infections encountered in immunodepressed individuals. The diagnosis of Pneumocystis pneumonia continues to be challenging due to the absence of specific symptoms in infected patients. Moreover, the standard diagnostic method employed for its diagnosis involves mainly PCR-based techniques, which besides being highly specific and sensitive, require specialized personnel and equipment and are time-consuming. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…36 New technologies (eg, biosensors) may provide an opportunity to determine the rate of airway colonization in healthcare workers using nasopharyngeal specimens. 37 In summary, our study showed occurrence of a ity. Multiple variables (ie, age, 12,28 sex, 38,39 type of allograft, 6,39 allograft rejection, 19,40 and immunosuppression 6,40 ) have been demonstrated to increase the risk of PCP following transplantation.…”
Section: Pcpsupporting
confidence: 52%
See 1 more Smart Citation
“…36 New technologies (eg, biosensors) may provide an opportunity to determine the rate of airway colonization in healthcare workers using nasopharyngeal specimens. 37 In summary, our study showed occurrence of a ity. Multiple variables (ie, age, 12,28 sex, 38,39 type of allograft, 6,39 allograft rejection, 19,40 and immunosuppression 6,40 ) have been demonstrated to increase the risk of PCP following transplantation.…”
Section: Pcpsupporting
confidence: 52%
“…Information related to exposure of healthcare workers to P. jirovecii are mainly limited to serologic data 36 . New technologies (eg, biosensors) may provide an opportunity to determine the rate of airway colonization in healthcare workers using nasopharyngeal specimens 37 …”
Section: Discussionmentioning
confidence: 99%
“…Several works have presented improved sensitivity of the detection of cytokines in complex biological fluids utilizing LSPR nanostructures or EOT nanohole arrays, which include detection of IL-1b, IL-18, TNF, and MMP-3 with LOD in low pg/mL and fg/mL (154)(155)(156)(182)(183)(184). The opportunities offered by these label-free optical biosensors are numerous since these devices can adopt a great variety of bioreceptors besides antibodies, including aptamers (185) and triplex-forming DNA probes (165,185) through different chemistry approaches (166) which can improve the detection of multiple cytokines, as well as enrich the analysis with other genetic and epigenetic biomarkers (167,168). Other labelfree optical biosensors based on silicon photonics, such as microring resonators, have been used for the simultaneous detection of pg/mL concentration of cytokines, including IL-2, IL-4, IL-5, and TNF (169).…”
Section: Label Free Biosensingmentioning
confidence: 99%
“…concentration). Our biosensor device has previously demonstrated its potential for clinical diagnostics in several areas, 35,38 including infectious diseases 34 and also for the direct detection of antibodies in human serum, 33,36 enabling a one-step, label-free, and sensitive and reliable detection. These features are crucial to develop a fast test with response times below 15-20 minutes (thanks to the no-need of secondary reagents or further signal amplification steps), and with the potential of providing quantitative information (i.e., the concentration range of antibodies in serum).…”
Section: Biosensor Assay Development and Analytical Characterizationmentioning
confidence: 99%